2012
DOI: 10.1159/000343407
|View full text |Cite
|
Sign up to set email alerts
|

Effects of AA Amyloidosis on Survival in Peritoneal Dialysis

Abstract: Background: To investigate the effects of ESRD etiologies on mortality in peritoneal dialysis patients. Methods: We included patients who initiated therapy between 2001-2011 and classified them according to etiologies including amyloidosis, diabetes mellitus, chronic glomerulonephritis and polycistic renal disease. Socio-demographic data, clinical courses and infectious complications were compared between groups, and the reasons for peritoneal dialysis withdrawal were recorded. Patient and technique survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…33,35 Decreased endothelial flow mediated diameter and increased carotid intima media thickness were proved in FMF patients, increasing the burden on kidneys. 36,37 On the other hand, renal amyloidosis was found to worsen the cardiovascular risk in FMF patients 38,39 and responsible for the worst prognosis among other etiologies of renal affection as regards the response to peritoneal dialysis 40 and posttransplantation morbidity and mortality. 41 Predictors of renal and/or urological affection in patients with FMF.…”
Section: Non-amyloid Kidney Disease (Nakd)mentioning
confidence: 99%
“…33,35 Decreased endothelial flow mediated diameter and increased carotid intima media thickness were proved in FMF patients, increasing the burden on kidneys. 36,37 On the other hand, renal amyloidosis was found to worsen the cardiovascular risk in FMF patients 38,39 and responsible for the worst prognosis among other etiologies of renal affection as regards the response to peritoneal dialysis 40 and posttransplantation morbidity and mortality. 41 Predictors of renal and/or urological affection in patients with FMF.…”
Section: Non-amyloid Kidney Disease (Nakd)mentioning
confidence: 99%
“…In such patients, a significant correlation was found between the serum albumin level and mortality (Zakharova, 2015); therefore, hypoalbuminemia in patients with amyloidosis can predict an increased risk of patient death (Ahbap et al, 2014). Further, Koc et al’s (2012) study demonstrated that catheter exit-site/tunnel infection was one of the significant and independent predictors of the survival rates of patients with amyloidosis.…”
Section: Introductionmentioning
confidence: 95%
“…Research has shown that patients with amyloidosis are significantly more likely to develop peritonitis ( p = .002) and catheter exit-site/tunnel infection ( p = .018) compared to patients with other etiologies of ESRF, including diabetes mellitus, chronic glomerulonephritis, and polycystic kidney disease (Koc et al, 2012). Catheter exit-site/tunnel infection has been reported as an independent predictor for patient survival (odds ratio: 0.250, p = .015) (Koc et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations